2018
DOI: 10.1093/ndt/gfy064
|View full text |Cite
|
Sign up to set email alerts
|

Defective gene expression of the membrane complement inhibitor CD46 in patients with progressive immunoglobulin A nephropathy

Abstract: Patients with progressive IgAN showed lower expression of mRNA encoding for the complement inhibitory protein CD46, which may implicate a defective regulation of C3 convertase with uncontrolled complement activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…They recently described a cohort of patients with biopsy-proven microangiopathy that was attributed clinically to severe hypertension; however, they found that 67% of patients had a mutation in the genes that encode complement factor C3 or the complement regulators CFH, CFI, or CD46, with concomitant evidence of complement activation in vivo, and poor renal outcome [39]. It would therefore be interesting to investigate whether IgA nephropathy patients with hypertension-associated microangiopathy share a similar genetic predisposition with the patients reported by Timmermans et al [39], particularly given the evidence that disease progression is more rapid in patients who have IgA nephropathy and a deficiency in complement regulation, as well as case reports describing atypical hemolytic uremic syndrome as a comorbidity in IgA nephropathy [18,[40][41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…They recently described a cohort of patients with biopsy-proven microangiopathy that was attributed clinically to severe hypertension; however, they found that 67% of patients had a mutation in the genes that encode complement factor C3 or the complement regulators CFH, CFI, or CD46, with concomitant evidence of complement activation in vivo, and poor renal outcome [39]. It would therefore be interesting to investigate whether IgA nephropathy patients with hypertension-associated microangiopathy share a similar genetic predisposition with the patients reported by Timmermans et al [39], particularly given the evidence that disease progression is more rapid in patients who have IgA nephropathy and a deficiency in complement regulation, as well as case reports describing atypical hemolytic uremic syndrome as a comorbidity in IgA nephropathy [18,[40][41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, very recently, expression pattern of CD46 and CD55 , both complement protein regulators were studied in the peripheral blood in patients with progressive IgAN nephropathy ( 27 ). The study showed that defective peripheral CD46 gene expression did not correlate with eGFR at sampling but with a faster annual loss of GFR.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the expression patterns of CD46 and CD55, both complement protein regulators, were studied in the peripheral blood in patients with progressive IgAN [ 65 ]. The study showed that defective peripheral CD46 gene expression did not correlate with eGFR at sampling, but with a faster annual loss of GFR [ 65 ].…”
Section: Mechanism Of Diseasementioning
confidence: 99%
“…Interestingly, the expression patterns of CD46 and CD55, both complement protein regulators, were studied in the peripheral blood in patients with progressive IgAN [ 65 ]. The study showed that defective peripheral CD46 gene expression did not correlate with eGFR at sampling, but with a faster annual loss of GFR [ 65 ]. Similarly, Cernoch et al [ 66 ], in a retrospective study of kidney-transplanted patients with IgAN recurrence, showed that there were no associations of eGFR with intrarenal CD46 complement transcripts, however they did describe the association of several intrarenal gene transcripts, including CD55, with CKD stage.…”
Section: Mechanism Of Diseasementioning
confidence: 99%